2008
DOI: 10.1093/eurheartj/ehn406
|View full text |Cite
|
Sign up to set email alerts
|

Long-term blinded placebo-controlled study of SNT-MC17/idebenone in the dystrophin deficient mdx mouse: cardiac protection and improved exercise performance

Abstract: AimsDuchenne muscular dystrophy (DMD) is a severe and still incurable disease, with heart failure as a leading cause of death. The identification of a disease-modifying therapy may require early-initiated and long-term administration, but such type of therapeutic trial is not evident in humans. We have performed such a trial of SNT-MC17/idebenone in the mdx mouse model of DMD, based on the drug’s potential to improve mitochondrial respiratory chain function and reduce oxidative stress.Methods and resultsIn thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 24 publications
4
58
0
Order By: Relevance
“…We observed no systolic dysfunction in 12-mo-old mdx mice, which is consistent with findings from Jearawiriyapaisarn et al (12). Previous reports suggest that systolic dysfunction may develop with age (15)(16)(17)(18). The reasons for these discrepancies are not known, but may be related to differences in the mdx strains used or perhaps other differences in genetic backgrounds.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed no systolic dysfunction in 12-mo-old mdx mice, which is consistent with findings from Jearawiriyapaisarn et al (12). Previous reports suggest that systolic dysfunction may develop with age (15)(16)(17)(18). The reasons for these discrepancies are not known, but may be related to differences in the mdx strains used or perhaps other differences in genetic backgrounds.…”
Section: Discussionsupporting
confidence: 90%
“…The same study also reported a reduction in several possible early markers of cardiomyopathy seen before the onset of cardiac dysfunction (8). It is well established that older mdx mice show an increase in cardiac mass and diastolic dysfunction (12,(15)(16)(17), providing us an excellent model to examine the effects of sildenafil on established cardiomyopathy. In fact, one study has reported the development of cardiac hypertrophy in mdx mice as early as 16 to 21 wks (12), suggesting that the reduced wall thickness we see in the chronically sildenafil-treated 12-mo-old mdx mice may be indicative of a long-term, sustained improvement.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, NF-κB activation is induced by several inflammatory mediators, such as IL-1β, TNFα, and metalloproteinases, all molecules found elevated in DMD [57,[98][99][100][101][102]. Active NF-κB is able to translocate to the nucleus, inducing the expression of genes encoding for cytokines and chemokines, cell adhesion molecules, and matrix metalloproteinases [103][104][105][106][107].…”
Section: Crosstalk Between Oxidative Stress and Inflammatory Responsementioning
confidence: 99%
“…67 Idebenone also ameliorated cardiac diastolic dysfunction and reduced mortality from systolic cardiac pump failure in this model. Considering the generally accepted limitation of the mdx mouse as an animal model for DMD, these potential benefits on skeletal muscle degeneration, endurance, and cardiac function would need to be confirmed in patients with DMD.…”
Section: This Mechanism Thereby Bypasses Complex I-dependent Elementioning
confidence: 72%